Pengaruh Regulasi Emosi dan Mindful Parenting Terhadap Kesiapan Anak Memasuki Taman Kanak-KanakThe Influence of Emotional Regulation and Mindful Parenting on Children's Readiness to Enter Kindergarten - Carina Rahadian Pratiwi; Cepi Safruddin Abdul Jabar (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
School readiness is the abilities that enable children to adapt successfully to the school environment, parental involvement is a crucial factor that supports school readiness. This study aims to examine the effect of emotional regulation and mindful parenting on children's kindergarten readiness using a quantitative correlational method with a sample of 306 parents of children aged 3–4 years in East Jakarta. Data were collected through three instruments: a kindergarten readiness questionnaire developed by the researcher, Emotional Regulation Checklist (ERC), and Mindfulness in Parenting Questionnaire (MIPQ). The validity test of the kindergarten readiness questionnaire yielded an Aiken's V of 0.892. Aiken's V values above 0.2 for the ERC, the validity of the MIPQ, through EFA–CFA, with acceptable fit indices: χ²/df = 2.8, CFI = 0.90, GFI = 0.96, RMSEA = 0.06, and RMSR = 0.04. Reliability testing showed high internal consistency, 0.954 for the readiness questionnaire, 0.788 for the ERC, and 0.941 for the MIPQ, confirming that the instruments are reliable. The preliminary test conducted before the hypothesis testing with normality, linearity, multicollinearity, and heteroskedasticity test. Hypothesis testing using multiple linear regression analysis show significant effects that both children’s emotional regulation and mindful parenting practices significantly contribute to children’s readiness for kindergarten. These results underscore the importance of continuous parental engagement in nurturing children’s developmental aspects to support a smoother transition into kindergarten.